Formação empreendedora na educação básica : uma análise das práticas implementadas no estado de Sergipe - Carvalho, Agair Juliete Cavalcante (2022)
This study aimed to carry out an analysis of the practices implemented for entrepreneurial training in Basic Education, in the state of Sergipe. For this purpose, four specific objectives were outlined: (1) to understand the perception about entrepreneurial education of professionals who work with entrepreneurial training in Basic Education (2) to describe and analyze the actions that managers Basic Education institutions, public and private, are carrying out in favor of the implementation of entrepreneurial training; (3) analyze the necessary factors for the implementation of entrepreneurial training in Basic Education; (4) understand the performance of institutions and actors that foster entrepreneurial training in Basic Education in the region studied. The research was based on three theoretical bases. First, the understanding of the phenomenon of entrepreneurship was presented, and later, a conception of entrepreneurial training was adopted, based on the development of a reflective, ethical and critical human being, who leads his own personal and professional life, whether acting as an employee or businessperson. Second, legal bases were identified that guide entrepreneurial education in educational institutions – reports from UNESCO, LDB, BNCC, DCNEB. To conclude this stage, factors considered fundamental for the implementation of entrepreneurial training in Basic Education were identified – tangible and intangible resources, training of education professionals and formation of collaborative networks. This research adopts a qualitative and interpretive approach. The semi-structured interview was the data collection instrument used and there was also document analysis and information available on official websites, which demonstrated the implementation of such an approach in the studied location. To capture new participants, after some limitations found in the field, the snowball sampling technique was chosen. Thus, 13 representatives of Basic Education institutions, public or private, that work with an entrepreneurial approach were appointed. The interpretation and analysis of data were separated into clusters, the first categorized the state public network of Sergipe and the second categorized the private education network in this region. In both, the categorizations comprised the analysis of the professionals' perceptions regarding entrepreneurial training in Basic Education, the actions developed in the schools where the interviewees work, the necessary factors for the implementation and development of such an approach and the performance of institutions and actors that promote it. The main results shows that the first steps were taken to implement practices aimed at entrepreneurial training in Basic Education in the state of Sergipe, but it cannot be said that there was an implementation in its entirety. The two clusters develop differently. The Covid-19 pandemic was represented as a variable that directly impacted the area of education as a whole, making entrepreneurial practices difficult, but not making them unfeasible. Public schools showed significant heterogeneity, mainly due to the lack of monitoring and control by the school administration and public manager. In the private schools, the practices implemented are based on a more homogeneous concept of entrepreneurial training, showing the beginning of the development of an entrepreneurial culture in the institution, but efforts are needed to allow integration between school and community, which is of fundamental importance for the approach studied. Finally, a booklet was prepared that will be made available to managers and teachers in the public and private network of Sergipe, with a concept and practical guidelines for the promotion of entrepreneurial training.